DECISION-MAKING THEORY IN FINANCIAL RISK MANAGEMENT: A CASE STUDY OF THE BANKING INDUSTRY - Zein Marsitta Rinales Silalahi; Khalishah Asti Salsabila; Narulika Ris Latifah; Rusdi Hidayat; Indah Respati Kusumasari (Publikasi Inspirasi Indonesia, 2024)
Decision making in financial risk management is an important element in maintaining financial stability and sustainability of the banking industry. This study aims to analyze relevant decision-making theories and their implementation in financial risk management in the banking sector. Case studies were conducted on several banks in Indonesia to explore the application of quantitative and qualitative methods in identifying, measuring, and managing financial risks. The approach includes analyzing credit risk, market risk, operational risk, and liquidity risk. The results show that data-driven decision-making by considering the theory of bounded rationality, prospect theory, and heuristic approach can improve the effectiveness of risk management. The study also underscores the importance of regulation, technology, and risk culture in supporting better decision-making. The findings provide strategic insights for practitioners and policy makers to optimize risk management in the banking industry.